2015
DOI: 10.4236/jdm.2015.54025
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Poor Sleep Quality among Type 2 Diabetes Mellitus Patients on Insulin Therapy

Abstract: The aim of this study is to investigate the possible risk factors of poor sleep quality among patients with type 2 diabetes mellitus on insulin therapy. The factors considered were age, sex, body mass index (BMI), glycosylated haemoglobin (HbA1c), duration of diabetes and depression. A total of 202 diabetic patients aged 20 years or older were included in the study. The results showed that female sex and depression were independent risk factors for poor sleep quality among type 2 diabetics on insulin therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
4
2
Order By: Relevance
“…There are some studies that showed the associations between poor sleep quality and insulin therapy[12,26,38]. The current study found that the odds of being poor sleeper increased as the level of psychological distress increased from 1.84 to 4.09.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…There are some studies that showed the associations between poor sleep quality and insulin therapy[12,26,38]. The current study found that the odds of being poor sleeper increased as the level of psychological distress increased from 1.84 to 4.09.…”
Section: Discussionsupporting
confidence: 49%
“…Regarding the negative effects of treatment with insulin on diabetic patients and reduction of satisfaction among patients treated with insulin injection[ 36 , 37 ], in the present study, the percentage of poor sleeper was a bit higher among those treated through insulin injection alone or with oral medication (40% compared to 39% in oral medication group) and much higher than other treatment group, though the difference was not statistically significant. There are some studies that showed the associations between poor sleep quality and insulin therapy[ 12 , 26 , 38 ]. The current study found that the odds of being poor sleeper increased as the level of psychological distress increased from 1.84 to 4.09.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the present study indicated that 57.3% of the subjects were classified as poor sleepers (PSQI> 5). The value obtained was higher compared to other studies conducted across the globe [ 8 - 9 ] which have reported 38 - 48 % 0f their subjects as “poor sleepers” but lesser as compared to a similar study conducted in India by Vigg et al [ 10 ].…”
Section: Discussioncontrasting
confidence: 75%
“…According to the findings of different studies, female gender, low income, longer disease duration, poor glycemic control, and presence of hypertension increases the risk of poor sleep quality among people with type 2 diabetes [10, 1618].…”
Section: Introductionmentioning
confidence: 99%